2015
DOI: 10.1117/1.jatis.1.3.034003
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the moisture absorption of thin carbon fiber reinforced plastic substrates for x-ray mirrors

Abstract: Abstract. We study a lightweight x-ray mirror with a carbon fiber reinforced plastic (CFRP) substrate for nextgeneration x-ray satellites. For tightly nested x-ray mirrors, such as those on the Suzaku and ASTRO-H telescopes, CFRP is the suitable substrate material because it has a higher strength-to-weight ratio and forming flexibility than those of metals. In flat CFRP substrate fabrication, the surface waviness has a root mean square (RMS) of ∼1 μm in the best products. The RMS approximately reaches a value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…We previously performed a precursor experiment for a moisture barrier in 2015. 31 In that experiment, both sides of a CFRP substrate were covered with a moisture barrier film, and it was noted that a moisture barrier film with low water-vapor transmissibility of <0.1 g • m −2 • day −1 showed high-barrier properties. In particular, a barrier film coated with SiO x worked well.…”
Section: Barrier Coatingmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously performed a precursor experiment for a moisture barrier in 2015. 31 In that experiment, both sides of a CFRP substrate were covered with a moisture barrier film, and it was noted that a moisture barrier film with low water-vapor transmissibility of <0.1 g • m −2 • day −1 showed high-barrier properties. In particular, a barrier film coated with SiO x worked well.…”
Section: Barrier Coatingmentioning
confidence: 99%
“…The swelling phenomenon is caused by moisture absorption, which originates from the resin. Sugita et al 31 measured the deformation of a CFRP substrate after drying and moisture absorption and found that the history of drying and moisture absorption influence the deformation. Thus, it is crucial to make the change of the moisture content in CFRP small, in order to suppress the deformation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations